Levocetirizine Withdrawal anxiety: A Case Report - Pun, Kiran Chandra; Thapa, Roshni; Mishra, Sanjeev Kumar (Journal of Psychiatrists’ Association of Nepal, 2025)
Levocetirizine, an antihistamine, is commonly prescribed for allergic conditions. The drug is often sold on an over the counter basis without any consideration of potential side effects or susceptibility to abuse. Here we present one such case who had withdrawal anxiety features after taking levocetirizine for a prolonged period which resolved after gradual tapering of levocetirizine under clonazepam coverage. Though second generation antihistamines do not cross the blood brain barrier and are believed to have no neurological effects, this case highlights the possibility that this may not be entirely true.